2014
DOI: 10.4236/aim.2014.45031
|View full text |Cite
|
Sign up to set email alerts
|

A Di-D-Fructose Dianhydride-Enriched Caramel Modulates Pig Fecal Microbiota Composition

Abstract: A correlation has been previously described between bifidobacteria counts before and after the use of a dietary additive in human studies. However, to our knowledge no information on this topic has yet been reported in animals, and no information exists either on similar possible correlations of bacterial groups other than bifidobacteria. The potential prebiotic effects of di-D-fructose dianhydride (DFA)-enriched caramels have been previously reported in laboratory animals, poultry and pigs. In the present wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Bacterial log 10 number of copies was determined in by using q-PCR. The 16S rRNA gene-targeted primers and PCR conditions used in this study were as previously described [13].…”
Section: Q-pcr Analysis Of Bacterial Groupsmentioning
confidence: 99%
“…Bacterial log 10 number of copies was determined in by using q-PCR. The 16S rRNA gene-targeted primers and PCR conditions used in this study were as previously described [13].…”
Section: Q-pcr Analysis Of Bacterial Groupsmentioning
confidence: 99%
“…Two approaches have been used to caramelize a sugar: heating at temperatures about the melting point, often in the presence of an homogeneous acid promotor , or using a heterogeneous solid catalyst as caramelization promotor, which allows lowering the temperature . The second approach has proven preferable in order to obtain DFA-enriched caramels for which prebiotic properties have been evidenced in several animal models. Although the heterogeneous conditions further complicate a kinetics analysis of DFA formation, several studies indicate that homogeneous models generally provide satisfactory results. For instance, Shan et al studied the hydration of cyclohexene in the presence of an ion-exchange resin and zeolites and found that a model representing a homogeneous system best fitted their experimental data.…”
Section: Introductionmentioning
confidence: 99%